Digital security and WhatsApp usage at school according to school administrators: A qualitative research - Yavaş Tuba; Gezer Mahmut (SHS Web of Conferences)
This research aims to identify the potential risks posed by WhatsApp instant messaging tool used as a communication tool in schools in terms of digital security according to the opinions of school administrators and to develop effective strategies against these risks. For this purpose, the research was conducted with a phenomenological design. In this context, face-to-face interviews were conducted with 12 school administrators at primary, secondary, and high school levels in the Antakya district of Hatay (Turkey). Data were collected through a semi-structured interview form. The data were subjected to content analysis. According to the findings; school administrators emphasized that tools such as WhatsApp provide many advantages in education, but also carry certain security and privacy risks. In this research, in addition to the advantages of the WhatsApp application for schools, its shortcomings in terms of “digital security”; were also revealed and it was suggested that a more secure application should be used for schools.